Aplikasi Finger Painting Terhadap Perkembangan Motorik Halus Pada An. M Usia Prasekolah Di Desa Karang Tengah Kecamatan Tanggeung Kabupaten Cianjur - Ermi Sri Nuning Saputri (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
Preschoolers are children aged 3 to 5 years. The problem of developmental disorders from year to year is still not resolved, especially in Indonesia, this incident is evidenced by as many as 16% of children under the age of five experiencing neurological and brain development disorders ranging from mild to severe. One of the actions that play a role in handling fine motor disorders in children is finger painting therapy. The purpose of this study was to apply finger painting to the fine motor development of An. M preschool age. This research design uses a case study method. The participant taken is one child who has delayed fine motor development in Karang Tengah Village. The data obtained from day 1-2 children still can't draw well, and on day 3 children start to be able to draw well. The results showed that there was an increase in the development of children's fine motor skills after being given the finger painting application.